The English Teacher in a College of Engineering - Sawyer, Thomas M. (Journal of Technical Writing and Communication, 1978)
There are two opposing views towards technical writing courses and towards teachers of technical writing: one favorable, the other disdainful. Those who disdain technical writing seem to believe that it: 1) imposes restrictive and arbitrary forms upon creative individuals, 2) involves only the accumulation of factual evidence, 3) deals with things, rather than with people, and 4) is, like other practical arts, a second-class activity. The first three beliefs are mistaken, and it can be argued that the dissemination of technical and scientific information is just as humanistic as artistic writing.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC83Z2Q2LTJ2YXAtOXc4cS0waHJ0